PENGABDIAN MASYARAKAT HEALTH EDUCATION (VIDEO ANIMASI & DEMONSTRASI) TENTANG PERTOLONGAN PERTAMA DISLOKASI BAHU METODE RICE PADA PMR DI SMAN 1 PAPAR - Didit Damayanti; Andika Siswoaribowo (STIKES dan AKZI Karya Husada Kediri, 2022)
School life is an important part of children's lives which has a direct impact on children's physical and mental health. The high physical activity carried out by school adolescents is one of the factors that causes dislocation conditions to occur in students. An accident or injury can become an emergency case and cause serious injury and even death if not handled properly. An accident or injury can become an emergency case and cause serious injury and even death if not handled properly. Improving the health status of the school community can be done through various activities, one of which is the provision of first aid training for sports injuries (sprain strain) using the RICE method. Students of SMAN I Papar are a group of teenagers in a community setting who have a risk of health problems due to dynamic activities. First aid for a sprain strain can be a treatment that can be given immediately. This is to prevent the injury from getting worse. One method that can be used to treat cases of sprain strain is RICE (Rest, Ice, Compress, Elevate) by keeping the leg that has sprain strain still, compressing it with ice or cold water to relieve pain, Giving elastic bandages to prevent swelling and also This can be done by elevating the injured body part to increase blood flow. Community service activities in the form of Sports Injury First Aid Training (Sprain Strain) at PMR SMAN I Papar are very positive activities to be carried out in order to disseminate health knowledge so as to increase the knowledge and ability of each student in providing assistance for shoulder dislocations.